Praktik Bekerja Aman Karyawan Bagian Rotary PT. Fairco Mawi Sulawesi Tengah - Hutabarat, Saut; Widjanarko, Bagoes; Wahyuni, Ida (Jurnal Promosi Kesehatan Indonesia, 2015)
ABSTRACTDevelopment in Indonesia has brought rapid progress in all areas of life such as industry, services, property, mining, transportation and others, but behind the progress of the negative impacts such as accidents, pollution and occupational diseases resulting in thousands of injuries and deaths every year. 85% of accidents are the result of the contribution of unsafe act. This research used a quantitative approach, explanatory research with a cross-sectional design. The population consists of 42 people drawn using total sampling method. Most dominant factors influencing safety driving practices of PO.X bus drivers are; knowledge (OR = 12,477), motivation (OR = 9,387), followed by attitude (OR = 7,855). Inadequate knowledge about the risks, dangers and accidents will make the worker indifferent and allow to perform unsafe acts and injure her self.Keywords : knowledge, motivation, employee rotary PT. Fairco Mawi